Just getting started - Bennett, Tony 1926-2023 (Harper, an imprint of HarperCollinsPublishers, 2016)
"Tony talks about Charlie Chaplin; Judy Garland; Dr. Martin Luther King, Jr.; Cole Porter; Amy Winehouse; Fred Astaire; Lady Gaga; members of his family; significant places and other wonders that have enriched his own life. Recounting his relations with these entertainers, humanitarians, and loved ones ... Tony reveals how he has been shaped by the principles each of them imparted to him."--Publisher description
Keywords: Bennett, Tony -- 1926-2023; Geschichte 1926-; Maler; Sänger; Schauspieler; USA; Bennett, Tony / 1926-; Singers / United States / Biography; BIOGRAPHY & AUTOBIOGRAPHY / Composers & Musicians; BIOGRAPHY & AUTOBIOGRAPHY / Entertainment & Performing Arts; Singers; United States; Autobiographies; Biography; Autobiografie; Biografie